Detection of CD133 (prominin‐1) in a human hepatoblastoma cell line (HuH‐6 clone 5). Issue 8 (27th May 2013) - Akita, Masumi; Tanaka, Kayoko; Murai, Noriko; Matsumoto, Sachiko; Fujita, Keiko; Takaki, Takashi; Nishiyama, Hidetoshi
ABSTRACT We examined CD133 distribution in a human hepatoblastoma cell line (HuH‐6 clone 5). We directly observed the cultured cells on a pressure‐resistant thin film (silicon nitride thin film) in a buffer solution by using the newly developed atmospheric scanning electron microscope (ASEM), which features an open sample dish with a silicon nitride thin film window at its base, through which the scanning electron microscope beam scans samples in solution, from below. The ASEM enabled observation of the ventral cell surface, which could not be observed using standard SEM. However, observation of the dorsal cell surface was difficult with the ASEM. Therefore, we developed a new method to observe the dorsal side of cells by using Aclar® plastic film. In this method, cells are cultured on Aclar plastic film and the dorsal side of cells is in contact with the thin silicon nitride film of the ASEM dish. A preliminary study using the ASEM showed that CD133 was mainly localized in membrane ruffles in the peripheral regions of the cell. Standard transmission electron microscopy and scanning electron microscopy revealed that CD133 was preferentially concentrated in a complex structure comprising filopodia and the leading edge of lamellipodia. We also observed co‐localization of CD133 with F‐actin. An antibody against CD133 decreased cell migration. Methyl‐β‐cyclodextrin treatment decreased cell adhesion as well as lamellipodium and filopodium formation. A decrease in the cholesterol level may perturb CD133 membrane localization. The results suggest that CD133 membrane localization plays a role in tumor cell adhesion and migration. Microsc. Res. Tech. 76:844–852, 2013. © 2013 Wiley Periodicals, Inc.